Peningkatan Motivasi dan Hasil Belajar Matematika pada Materi Penjumlahan dan Pengurangan Bilangan Dua Angka melalui Model Problem Based Learning di Kelas II MIN 2 Pasaman - Yulismar, Yulismar (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This classroom action research addresses low motivation and learning outcomes in mathematics among second-grade students at MIN 2 Pasaman, focusing on two-digit addition and subtraction. To improve student motivation and mastery through Problem-Based Learning (PBL). A two-cycle PTK (Kemmis & McTaggart) was implemented with 23 students. Instruments included pre-/post-tests, motivation questionnaires, observation sheets, and documentation. Pre-intervention mastery was 43% (mean score 65). After Cycle I, mastery rose to 61% (mean 74) and after Cycle II to 91% (mean 86). Motivation (high category) increased from 48% to 87%. Conclusions: PBL effectively improved both motivation and learning outcomes.